The Role of Pre-School Education in the Child's Development and Analysis of Current Pre-School Education System in Uzbekistan - Nigora Mamadaminova (Vasyl Stefanyk Precarpathian National University, 2021)
The author of the article attempts to analyze the current pre-school education system of Uzbekistan, its main challenges, shortcomings and reforms. Moreover, this research will provide the study of the importance of learning at early ages (3-5) and its impact on the future learning and personal development of children. The research highlights the analysis of domestic and foreign prospects of the studied issue. Namely, the researcher presents the view that developed countries pay more and more attention to boost the quality of pre-school educational institutions, the efficiency of curriculum, and implementation of more social activities to enhance the development of children's soft skills; however, this is not the case in developing countries such as Uzbekistan. Thus, the goal of the paper would be to elaborate on the need to consider, remodel and upgrade the pre-school education system further and trigger to start some campaigns which will aim to develop young mother's personal and professional development. The study will highlight the impact of pre-school education by evaluating the literature in the field, looking deeper at the experience of developed countries as well as considering the situation in Uzbekistan regarding the mentioned area. The findings of the paper can be deployed to prepare educational policy and contribute to the development of the entire education system of Uzbekistan.